ANALYSIS OF FACTORS INFLUENCING IMPORT DOCUMENT DELAYS AND THEIR IMPACT ON STORAGE AND DEMURRAGE COSTS AT PT ALSTOM GRID INDONESIA - Simarmata, Andre Yosafat; Simarmata, Juliater (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to analyze the factors that cause delays in import documentation and their impact on storage and demurrage costs at PT Alstom Grid Indonesia. Delays in customs clearance and document submission often generate significant financial losses for the company due to additional port charges. The research employed a qualitative method with an exploratory approach, supported by descriptive data. Data were collected through questionnaires, interviews, observations, and company document archives. The Fishbone Diagram and 5 Why Keys analysis were applied to identify the root causes of import documentation delays. The findings imply that improving interdepartmental coordination, strengthening employee training, and ensuring consistent compliance with standard operating procedures are critical to minimizing import documentation delays. By addressing these root causes, PT Alstom Grid Indonesia can reduce avoidable logistics costs and improve efficiency in international trade operations.